Unexpected Learning: Development of the CoP and Its Members #generational-shift - Carol A Olszewski MA, MT-BC; Kyle A Znamenak MA; Keli B Pontikos MA; Toni M. Paoletta MEd; Catherine A Hansman PhD; Karie A Coffman PhD; Matthew L Selker MPA (Adult Education Research Conference, 2019)
Our research explores how multigenerational CoPs may provide graduate students, particularly doctoral students, the space to explore and develop their professional identities and find their scholarly voices.
Keywords: Community of Practice; adult learners; intergenerational; multigenerational